2021
DOI: 10.3390/cells10050997
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Inhibitors of Dynamin Exert Differential Effects in VEGF Signaling

Abstract: VEGFR2 is the main receptor and mediator of the vasculogenic and angiogenic activity of VEGF. Activated VEGFR2 internalizes through clathrin-mediated endocytosis and macropinocytosis. As dynamin is a key regulator of the clathrin pathway, chemical inhibitors of dynamin are commonly used to assess the role of the clathrin route in receptor signaling. However, drugs may also exert off-target effects. Here, we compare the effects of three dynamin inhibitors, dynasore, dyngo 4a and dynole, on VEGFR2 internalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…However, in many cases, the results were discussed without considering the cross‐effects of inhibitors. Thus, the specificity of these inhibitors and their potential unexpected effect on other cellular functions were not enough documented, although some published works indicated off‐target effects of endocytosis inhibitors 45–48 . We previously observed that well‐known endocytosis inhibitors (Table S1) had negligible inhibitory effects, lacked specificity on the cellular uptake of endocytosis markers (Tf, CTB, and dextran), or reduced cell viability 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in many cases, the results were discussed without considering the cross‐effects of inhibitors. Thus, the specificity of these inhibitors and their potential unexpected effect on other cellular functions were not enough documented, although some published works indicated off‐target effects of endocytosis inhibitors 45–48 . We previously observed that well‐known endocytosis inhibitors (Table S1) had negligible inhibitory effects, lacked specificity on the cellular uptake of endocytosis markers (Tf, CTB, and dextran), or reduced cell viability 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the specificity of these inhibitors and their potential unexpected effect on other cellular functions were not enough documented, although some published works indicated off-target effects of endocytosis inhibitors. [45][46][47][48] We previously observed that well-known endocytosis inhibitors (Table S1) had negligible inhibitory effects, lacked specificity on the cellular uptake of endocytosis markers (Tf, CTB, and dextran), or reduced cell viability. 14 For example, sucrose, a clathrin-mediated endocytosis inhibitor, completely abolished the cellular uptake of all endocytosis markers.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work showed that chemical inhibitors of dynamin may exert additional inhibitory effects on signaling independent of the blockage of its target dynamin. These off-target functions were evidenced when genetic approaches to block dynamin gave opposite results (Basagiannis et al, 2017; Basagiannis et al, 2021; Park et al, 2013; Persaud et al, 2018). We have previously demonstrated that both Dyngo-4a treatment and DynK44A overexpression block CRHR1 endocytosis after ligand stimulation causing a diminished cAMP response and a blockage of the sustained ERK1/2 activation phase in HT22-CRHR1 cells (Bonfiglio et al, 2013; Inda et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In Drosophila, Slit-induced endocytosis of Robo and subsequent axonal repulsion have been shown to be dynamin-and clathrin-dependent, and to require AP2-binding motifs present in the cytoplasmic domain of ROBO-1 (Chance and Bashaw, 2015). We, therefore, used Dyngo-4a, a potent dynamin inhibitor (McCluskey et al, 2013, Basagiannis et al, 2021 Similar to Robo in Drosophila (Chance and Bashaw, 2015), we found that human ROBO-1 also contains two AP2-binding motifs (Yxxφ) (Collins, 2002)…”
Section: Nslit2-induced Endocytosis Of Robo1 From the Cell Surface Is...mentioning
confidence: 99%